Antibacterial, injectable, and adhesive hydrogel promotes skin healing - Fang, Zilong; Lin, Tao; Fan, Shuai; Qiu, Xing; Zhong, Ziqing; Yang, Ganghua; Yang, Jianqiu; Zhang, Guoqing; Feng, Yang; Ai, Fanrong; Shi, Qingming; Wan, Wenbing (Frontiers in Bioengineering and Biotechnology, 2023)
With the development of materials science, injectable hydrogels with anti-bacterial, adhesive, and wound-healing properties have become commonplace. However, injectable hydrogels with simple synthetic methods, low cost, antibacterial properties and wound healing promotion are rare. In this paper, a novel injectable hydrogel wound dressing based on carboxymethyl chitosan (CMCS) and polyethyleneimine (PEI) was constructed. Since CMCS is rich in -OH and -COOH, and PEI is rich in -NH2, the two can interact through strong hydrogen bonds, and it is theoretically feasible to form a gel. By changing their ratio, a series of hydrogels can be obtained by stirring and mixing 5wt% CMCS aqueous solution and 5wt% PEI aqueous solution at volume ratios of 7:3, 5:5, and 3:7, respectively. Characterized by morphology, swelling rate, adhesive, rheological properties, antibacterial properties, in vitro biocompatibility and in vivo animal experiments, the hydrogel has good injectability, biocompatibility, and antibacterial properties With a certain adhesive, it can promote the growth and repair of cells, and has broad application prospects.